The Empowerment of Dasa Wisma as Partners in the Prevention and Control of Drug Abuse in Teenagers in Ratu Agung Sub-District of Bengkulu City - Samidah, Ida; Susiwati, . (KnE Life Sciences, 2021)
Teenagers are a vulnerable demographic with regards to the risk of becoming drug users. The high levels of drug abuse at a young age in Indonesia are a growing source of concern. Effective drug abuse prevention needs to start with primary prevention by individuals, families, groups and communities. This study evaluates the empowerment of Dasa Wisma and the homestead program, to identify the influence of the empowerment of Dasa Wisma through partnership on the effectiveness of anti-drug cadres and families in the Ratu Agung Sub-district of Bengkulu City. This research type is quantitative with quasi-experimental design. The design used was pre-test and post-test with control group design (quasi-experiment with control). While the treatment group who felt empowered counted 34.78%, the control group only 12.5% felt empowered, with P value = 0.00. The empowerment of Dasa Wisma affects knowledge, attitude, perception, religiosity, use of spare time, peer group, family harmony and family communication with value P = 0.00. It also affects the liveliness of anti-drug cadres with a value of P = 0.008. Dasa Wisma affects the family activeness in the prevention and control of drugs in teenagers with a value of P = 0.00. Conclusion: it can be concluded that the empowerment of Dasa Wisma as a partner in Ratu Agung sub-district of Bengkulu affects the prevention and tackling of drug abuse in teenagers, either by anti-drug cadres or by family. Keywords: Empowerment, Dasa Wisma, partner, drugs